Characteristics of long stay home care clients’ acute care use who live with frailty in Alberta, Canada: A retrospective cohort study - Jananee Rasiah; Andrea Gruneir; Jeffrey Poss; Jayna Holroyd-Leduc; Greta G. Cummings (PLoS ONE, 2026)
Objective To describe the characteristics of long stay home care clients’ acute care use who live with frailty, and to compare associated factors for hospitalizations. Methods The cohort comprised individuals 65 to 104 years old (n=10,107) who were observed from 2015-2017. Population-based administrative data were linked by individual records, descriptive statistics were reported, and logistic regression models were run. Results Majority of clients were female (69.7%), and the largest proportion of clients were 75-84 years old. Arthritis (65.6%) and hypertension (74.5%) were most prevalent in clients who were frail. Frail clients (40.6%) had between 1-3 emergency department visits. Mean length of stay was 16.6 days for frail hospitalized clients. Being pre-frail and frail were associated factors for hospitalization. Conclusion Further research is needed to determine the risk classification of more factors, such as social characteristics that predispose home care clients with frailty to hospitalization.